2014
DOI: 10.4012/dmj.2013-121
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of adhesion of reline resins to the thermoplastic denture base resin for non-metal clasp denture

Abstract: This study aimed to evaluate the tensile and transverse bond strength of chairside reline resins (Tokuyama Rebase II, Mild Rebaron LC) to a thermoplastic acrylic resin (Acrytone) used for non metal clasp denture. The results were compared with those of a conventional heat polymerized acrylic resin (Paladent 20) and a thermoplastic polyamide resin (Biotone). The failure sites were examined by scanning electron microscopy to evaluate the mode of failure. As results, the bond strength of reline resins to a thermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 17 publications
2
35
0
3
Order By: Relevance
“…Several types of polyamides are most commonly used, having the longest history among the thermoplastic resins used for NMCDs 2) . Several studies have evaluated the properties of polyamide denture base materials, such as their flexural properties 1,5,6) , water sorption 1,7,8) , color stability 1,4,7) , bond strength to acrylic resins 9,10) , dimensional accuracy 11) , and surface roughness 4,12) . According to the results of these studies, polyamides were thought to be an alternative to the conventional acrylic resins due to their esthetic and functional characteristics and physical properties such as thermo-injectability, high impact strength and flexibility.…”
Section: Introductionmentioning
confidence: 99%
“…Several types of polyamides are most commonly used, having the longest history among the thermoplastic resins used for NMCDs 2) . Several studies have evaluated the properties of polyamide denture base materials, such as their flexural properties 1,5,6) , water sorption 1,7,8) , color stability 1,4,7) , bond strength to acrylic resins 9,10) , dimensional accuracy 11) , and surface roughness 4,12) . According to the results of these studies, polyamides were thought to be an alternative to the conventional acrylic resins due to their esthetic and functional characteristics and physical properties such as thermo-injectability, high impact strength and flexibility.…”
Section: Introductionmentioning
confidence: 99%
“…3 Therefore, the bond strength of the TDBR's may be affected if used clinically and surface modification is necessary to enhance the bond strength between the thermoplastic denture base resin and relining resin. Several studies showed that the use of silica coating, 12,18 acetic acid, 9 and tribochemical silica coating combined with 4-methacryloyloxyethy trimellitate anhydride (4-META)/ methyl methacrylate (MMA) -tributylborane (TBB) 3 can improve the strength between denture bases. Although there were many attempts to improve the adhesive properties of denture base resin, limited research has been focused on thermoplastic denture base resin material.…”
Section: Discussionmentioning
confidence: 99%
“…1,9-11 Therefore, it does not provide sufflcient bond strength to autopolymerized resins for repairing fractured dentures or replacing dislodged teeth. 9,10,12 Plasma treatment has been used to modify the surface of products in the industrial world. 13 Nonthermal plasma (NTP) treatment is made of partially ionized gas with ions, electrons, and uncharged particles such as atoms, molecules, and radicals.…”
Section: 대한치과보철학회지 56권 3호 2018년 7월mentioning
confidence: 99%
“…The flexural and impact strength of polyamide polymers are higher than those of heat-cured denture base materials 12345. Nevertheless, the repair strength of auto-polymerized resins to polyamide polymers is too weak, and the repair mostly requires laboratory procedures 6789…”
Section: Introductionmentioning
confidence: 99%
“…Polyamide is a thermoplastic material produced by a condensation reaction between a diamine and a dibasic acid 714. The chemical resistance of polyamide polymers is due to their high degree of crystallinity; the penetration of monomer molecules and other resin primers into the polymers is difficult 3815. Therefore, nylon polymers do not provide sufficient bond strength to auto-polymerized resins for repairing fractured denture or replacing dislodged denture teeth 89…”
Section: Introductionmentioning
confidence: 99%